General practice variation in peptic ulcer prophylaxis: a nationwide register-based study - Peter Fentz Haastrup; Jane Møller Hansen; Jens Søndergaard; Dorte Ejg Jarbøl (Scandinavian Journal of Primary Health Care)
Background Incidence of peptic ulcer bleeding can be substantially reduced by prophylactic use of proton pump inhibitors (PPIs) in patients at risk, but use of PPI varies among risk patients, and substantial under-prescribing may exist. The variation in prophylactic prescribing among general practices remains unknown.Methods A nationwide register-based cross-sectional study analyzing the proportion of patients at risk of ulcer bleeding receiving PPI treatment within Danish general practices. Using logistic regression, we analyze associations between general practice characteristics and prophylactic treatment among patients at risk of ulcer bleeding listed with the general practice.Results In most general practices, less than 40% of the patients at increased risk of ulcer bleeding were covered by PPI. Geographical variation was present, where practice location outside the capital area was associated with higher odds of PPI coverage among their risk patients. Partnership practices with GPs with a mean age ≥65 years or with only female GPs were associated with higher odds of providing prophylaxis among their risk patients compared to practices with a mean GP age <45 years or with only male GPs. Similar associations were not found for single-handed practices.Conclusions A significant under-prescribing of ulcer prophylaxis is common across all general practice characteristics, and only few associations with practice characteristics were present. Most efforts to rationalize PPI prescribing have aimed at reducing overprescribing but the findings point to under-prescribing as a problem as well. Development of new methods to assist GPs in identifying individuals at risk of ulcer complications is needed.